Baixo esplendor, de Marçal Aquino: diálogo entre amor e violência - Barbosa, Larissa Ferreira (2023)
The present work aims to analyze the novel Baixo esplendor, by Marçal Aquino (2021), following the structure of the violent and aggressive reality, as well as the reflection on the social and cultural obstacles of the lives of the characters, considering the effects of the borderline points between fiction and reality in the love story and the underworld and its effects on the production of the narrative arising from the world of crime. The research problem involves the following questions: How are the love stories of the novel traced and plotted in the Brazilian underworld? How are the thematic traits of violence configured from the portrait of reality? To what extent does the aforementioned novel present a similar and different narrative structure from the traditional model of detective novels? The hypotheses that guided the study were: Baixo esplendor is composed of stories traced in keys of mystery and seduction, built by the emotion of eroticism and violence, fundamental pieces for the construction of the web of social, loving, poetic, and psychological conflicts in the narrative; the novel weaves a “portrait of reality” through the representation and characterization of the characters, time and space of the narrative; the narrative is structured in crime fiction, promoting a kind of reinvention of realism, exposing the effects of reality. The theoretical apparatus involved Roland Barthes, Nadiá P. Ferreira, Karl Erik Schollhammer, and Phyllis Dorothy James, among others. The structure of this study is divided into three chapters: the first presents the author, discusses his way of writing, and presents crime fiction; the second chapter analyzes the relationship between reality and fiction within the novel; and the third, analyzes the theme of love and violence that configures the narrative and exposes the Brazilian underworld. From this work with the novel, in a tense game between fiction and reality, social criticism, and an immersion in the suburban world, the relationship between love and violence can be apprehended